2017
DOI: 10.1371/journal.pone.0178278
|View full text |Cite
|
Sign up to set email alerts
|

Fluvastatin inhibits AGE-induced cell proliferation and migration via an ERK5-dependent Nrf2 pathway in vascular smooth muscle cells

Abstract: Advanced glycation endproduct (AGE)-induced vascular smooth muscle cell (VSMC) proliferation and reactive oxygen species (ROS) production are emerging as important mechanisms of diabetic vasculopathy, but little is known about the molecular mechanism responsible for the antioxidative effects of statins on AGEs. It has been reported that statins exert pleiotropic effects on the cardiovascular system due to decreases in AGE-induced cell proliferation, migration, and vascular inflammation. Thus, in the present st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 50 publications
0
16
0
1
Order By: Relevance
“…HO-1 and NQO1 are the crucial downstream of Nrf2, which are involved in Nrf2-mediated protective effect on injured endothelial cells [20,21]. Therefore, we detected expression of HO-1 and NQO1 with western blotting.…”
Section: Nrf2 Activation Is Associated With Protective Effect Of Zedomentioning
confidence: 97%
“…HO-1 and NQO1 are the crucial downstream of Nrf2, which are involved in Nrf2-mediated protective effect on injured endothelial cells [20,21]. Therefore, we detected expression of HO-1 and NQO1 with western blotting.…”
Section: Nrf2 Activation Is Associated With Protective Effect Of Zedomentioning
confidence: 97%
“…To gain insight into the mechanism of this priming effect, we tested the following two potential mechanisms: (a) decreased expression of antioxidants and (b) TL shortening, both of which are known senescent phenotypes, as we discussed in the Introduction. We previously reported that ERK5 transcriptional activity, but not kinase activity, is inhibited by p90RSK activation which induces ERK5 S496 phosphorylation in endothelial cells 14 , and others have shown that ERK5 can up-regulate the activity of NRF2, which is a transcription factor that is well known to regulate antioxidant expression 23,24 . Therefore, we hypothesized that p90RSK activation, induced by cART, inhibits NRF2 activity and antioxidant expression via ERK5 S496 phosphorylation.…”
Section: Cart Primes Monocytes and Macrophages To Oxidative Stress Bymentioning
confidence: 99%
“…In addition to a lipid-lowering effect, statins appear to protect against pathomechanisms associated with the NRF2 network such as inflammatory (Pantan et al, 2016;Wu et al, 2016a;Hwang et al, 2017) and pathologic ROS formation (Abdanipour et al, 2014). They are competitive inhibitors of 3-hydroxy-3-methyl-glutaryl-CoA reductase, which catalyzes the rate-limiting reaction in cholesterol synthesis.…”
Section: E Repurposing Instead Of De Novo Drug Discovery and Developmentioning
confidence: 99%